Nursing Procedures for the Prevention and Treatment of Mucositis Induced by Cancer Therapies: Clinical Practice Guideline Based on an Interdisciplinary Consensus Process and a Systematic Literature Search. (January 2021) - Steinmann, Diana; Babadağ Savaş, Burcu; Felber, Sabine; Joy, Sosamma; Mertens, Isabelle; Cramer, Holger; Paul, Anna; Layer, Monika; Klafke, Nadja; Stolz, Regina; Heyder, Ute; Neuberger, Petra; et al.
Background: Patients with cancer receiving tumor therapy often suffer from oral mucositis. Objectives: The aim of this project was to summarize experiences with nursing procedures by experts in integrative oncology and to establish recommendations for nursing interventions that can prevent or cure mucositis. Methods: The study design was an interdisciplinary consensus process based on a systematic literature search. Results: The panel discussed and agreed on 19 nursing procedures, which included mouthwashes, such as teas, supplements, oil applications, and different kinds of ice cubes to suck, as well as flaxseed solution, propolis, and mare milk. Twelve interventions were classified as effective, with effectiveness for OraLife, propolis, sea buckthorn pulp oil, marshmallow root tea also for xerostomia, Helago chamomile oil, mare milk, and Saliva Natura rated as highly effective in clinical experience. In the systematic literature search, a total of 12 out of 329 randomized controlled trials and meta-analyses on chamomile (n = 3), Calendula (n = 1) and sage (n = 1), propolis (n = 2), and sucking ice cubes (cryotherapy; n = 5) met all inclusion criteria. Trial evidence for effectiveness in oral mucositis was revealed for propolis and cryotherapy. Conclusions: The current evidence supports the use of some nursing procedures (f.e. propolis for 2 and 3 grade mucositis) for improving oral mucositis during cancer therapies. There is still a need to define general clinical practice guidelines for the supportive treatment of mucositis, as well as for more interdisciplinary research in this area.